USE OF INTERACTIVE METHODS IN THE DEVELOPMENT OF ORAL SPEECH - Rahmatullayeva Mukhlisa Abdugani qizi (American Journals, 2024)
This article provides information about some of the interactive methods that serve in the development of oral speech skills of students in general education schools. Information on the types and characteristics of interactive methods and their effect on students is provided.
Keywords: Oral speech, pupils, interactive methods, essential skills, competency, significant knowledge.